Winter dialogue : poems - Venclova, Tomas; Miłosz, Czesław; Senechal, Diana (1997)
Diana Senechal's deft translation from the Lithuanian - done in collaboration with the author - preserves both Venclova's lyric voice and the complex stanzaic patterns for which his poetry is known in his native country. Featuring an insightful introduction by the late Joseph Brodsky, and a fascinating exhange between Venclova and Nobel laureate Czeslaw Milosz about the city of their respective youths